Planning (1997)
- Why do we need a training plan ? - What is the purpose of a Training Plan ? - What information needs to be gathered ? - What are the phases of a training year ? - What if there is an Indoor and an outdoor season ? - What are the objectives of each phase ? - What are the activities of each Phase ? - How do I prepare a plan ? - What are a training unit and a training session ?